High Intensity Training May Reverse the Fiber Type Specific Decline in Myogenic Stem Cells in Multiple Sclerosis Patients - Farup, Jean; Dalgas, Ulrik; Keytsman, Charly; Eijnde, Bert O.; Wens, Inez (Frontiers in Physiology, 2016)
Multiple sclerosis (MS) is associated with loss of skeletal muscle mass and function. The myogenic stem cells (satellite cells – SCs) are instrumental to accretion of myonuclei, but remain to be investigated in MS. The present study aimed to compare the SC and myonuclei content between MS patients (n=23) and age matched healthy controls (HC, n=18). Furthermore, the effects of 12 weeks of high intensity training on SC and myonuclei content were explored in MS. Muscle biopsies were obtained from m. Vastus Lateralis at baseline (MS+HC) and following 12 weeks of training (MS only). Frozen biopsies were sectioned followed by immunohistochemical analysis for fiber type specific SCs (Pax7+), myonuclei (MN) and central nuclei content and fiber cross-sectional area (fCSA) using ATPase histochemistry. At baseline the SCs per fiber was lower in type II compared to type I fiber in both MS (119%, p<0.01) and HC (69%, p<0.05), whereas the SCs per fCSA was lower in type II fibers compared to type I only in MS (72%, p<0.05). No differences were observed in MN or central nuclei between MS and HC. Following training the type II fiber SCs per fiber and fCSA in MS patients increased by 165% (p<0.05) and 135% (p<0.05), respectively. Furthermore, the type II fiber MN content increased by 35% (p<0.05) following training. In conclusion, the SC content is lower in type II compared to type I fibers in both MS and HC. Furthermore, high intensity training was observed to selectively increase the SC and myonuclei content in type II fibers in MS patients.